The Effect of Lenalidomide Ointment on TNF-α Tissue Levels in Mice with Imiquimod-Induced Psoriasis - Mustafa Thamer, Sajjad; Q. Yahya, Mohammed (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Lenalidomide is an immunomodulatory drug having notable anti-inflammatory, and anti-antineoplastic properties. Lenalidomide suppresses the production of pro-inflammatory cytokines that have been linked to a variety of hematologic malignancies. Lenalidomide enhances the immune system of the host by regulating T cell proliferation, which results in changes in inflammation that are related to the etiology of psoriasis. Objectives: The objectives of this study were to determine the efficacy of lenalidomide as an ointment in treating mouse models of psoriasis as well as how it may affect TNF-α levels in skin tissue in different experimental groups. Methods: The study was carried out between November 2021 and June 2022. 70 healthy male albino mice were randomly divided into 7 groups of 10 animals each. In groups (1, 2, 3, 4, 5 and 6), imiquimod produced psoriasis. Only imiquimod cream was administered to Group 1, after psoriasis induced, Clobetasol ointment was applied to Group 2, placebo ointment was applied to Group 3, and lenalidomide ointment (1%, 2%, and 3%) were applied to Groups (4, 5, and 6), respectively. Healthy mice were utilized as a comparative control in Group 7. SPSS was utilized for the statistical analysis of the data (version 26). Results: Following lenalidomide treatment, the psoriatic region improved. Lenalidomide’s effectiveness to treat imiquimod-induced mouse psoriasis was explained by the difference in tissue levels of TNF-α between the examined groups. Conclusions: Findings suggest that different concentrations of lenalidomide ointment can improve mouse models of imiquimod-induced psoriasis. Histopathology and immunohistochemistry assays show that lenalidomide ointment was more effective and had no side effects that were associated with the use of the standard drugs.